Mała fibula pod dużym kamieniem, czyli o badaniach archeologicznych nad Słudwią - Rutkowski, Wojciech; Janiak, Radosław (Folia Praehistorica Posnaniensia, 2025)
In the autumn of 2019, a stone structure was uncovered in Buszków Dolny, located within Żychlin commune, Kutno county. Excavations were carried out on the 8th and 9th of November, 2019. The central feature of the site was a large, elongated glacial erratic, surrounded by smaller stones forming an enclosure. Beneath this structure, a small oval pit, distinct against the yellow sand, was identified. In the eastern section of the pit, a heavily corroded, unburnt iron fibula was discovered and classified as Type A158, Group VI, according to O. Almgren’s typology. The analysis of this metal artefact was funded by the National Science Centre, Poland (grant no. 2024/08/X/HS3/00280). This discovery is part of a broader pattern of object deposition under large stones associated with the Przeworsk culture, which inhabited the Bzura River basin during the Roman period. The deposit from Buszków Dolny finds its closest parallels in the cemeteries in Mnich, Kutno county, and Patoki. In both instances, no human bones or charcoal were found within the pit fill.